2023
DOI: 10.3390/cells12020314
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II Presentation in Autoimmunity

Abstract: Antigen presentation by major histocompatibility complex class II (MHC-II) molecules is crucial for eliciting an efficient immune response by CD4+ T cells and maintaining self-antigen tolerance. Some MHC-II alleles are known to be positively or negatively associated with the risk of the development of different autoimmune diseases (ADs), including those characterized by the emergence of autoreactive T cells. Apparently, the MHC-II presentation of self-antigens contributes to the autoimmune T cell response, ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 172 publications
0
11
0
Order By: Relevance
“…All four proteins belong to the MHC II class, which is essential for triggering an effective immune response to CD4 T cells and maintaining autoantigen tolerance. 36 However, we did not find significant differences in the expressions of these four genes in the expression profile analysis of psoriatic lesions based on GEO datasets, which needs more experiments to prove.…”
Section: F I G U R E 3 Multiomics Analysis Of the Underlying Mechanis...mentioning
confidence: 64%
“…All four proteins belong to the MHC II class, which is essential for triggering an effective immune response to CD4 T cells and maintaining autoantigen tolerance. 36 However, we did not find significant differences in the expressions of these four genes in the expression profile analysis of psoriatic lesions based on GEO datasets, which needs more experiments to prove.…”
Section: F I G U R E 3 Multiomics Analysis Of the Underlying Mechanis...mentioning
confidence: 64%
“…However, it has been reported that the genetic implementation of antigenic minigenes can elicit lower reactivity compared to the exogenous loading of antigenic fragments ( Parkhurst et al, 2019 ). Exogenous loading of peptides may also require competitive displacement of the peptide already presented on MHC-II, which can be problematic when exogenous loading is required for low-affinity peptides that may still be presented and elicit T-cell responses under physiological conditions ( Stadinski et al, 2010 ; Yang et al, 2014 ; Ishina et al, 2023 ). In our system, each peptide of interest is covalently bound to the beta chain of the MHC-II molecule, allowing for the presentation of low-affinity peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their transcriptomic signature also revealed higher expression levels of MHC class II autoantigens and Aβ binding receptor genes. It was previously reported that MHC class II autoantigen-expressing microglia were associated with various autoimmune-related neurodegenerative diseases and the development of chronic inflammatory lesions [ 116 119 ], which hinted at an intrinsic pathological nature of these cells. In addition to these gain-of-function genes, downregulated genes in FDAMic also suggested a loss in phagocytic activities, which may render them ineffective in clearing Aβ and other protein aggregates from the region [ 120 ] despite exhibiting Aβ binding properties.…”
Section: Discussionmentioning
confidence: 99%